Traumatic colon injury in damage control laparotomy—A multicenter trial: Is it safe to do a delayed anastomosis?. Issue 4 (April 2017) - Tatebe, Leah Carey; Jennings, Andrew; Tatebe, Ken; Handy, Alexandra; Prajapati, Purvi; Smith, Michael; Do, Tai; Ogola, Gerald O.; Gandhi, Rajesh R.; Duane, Therese M.; Luk, Stephen; Petrey, Laura Bruce
Abstract : Background: Delayed colonic anastomosis after damage control laparotomy (DCL) is an alternative to colostomies during a single laparotomy (SL) in high-risk patients. However, literature suggests increased colonic leak rates up to 27% with DCL, and various reported risk factors. We evaluated our regional experience to determine if delayed colonic anastomosis was associated with worse outcomes. Methods: A multicenter retrospective cohort study was performed across three Level I trauma centers encompassing traumatic colon injuries from January 2006 through June 2014. Patients with rectal injuries or mortality within 24 hours were excluded. Patient and injury characteristics, complications, and interventions were compared between SL and DCL groups. Regional readmission data were utilized to capture complications within 6 months of index trauma. Results: Of 267 patients, 69% had penetrating injuries, 21% underwent DCL, and the mortality rate was 4.9%. Overall, 176 received primary repair (26 in DCL), 90 had resection and anastomosis (28 in DCL), and 26 had a stoma created (10 end colostomies and 2 loop ileostomies in DCL). Thirty-five of 56 DCL patients had definitive colonic repair subsequent to their index operation. DCL patients were more likely to be hypotensive; require more resuscitation; and suffer acute kidney injury, pneumonia, adult respiratory distress syndrome, and death. Five enteric leaks (1.9%) and three enterocutaneous fistulas (ECF, 1.1%) were identified, proportionately distributed between DCL and SL ( p = 1.00, p = 0.51). No difference was seen in intraperitoneal abscesses ( p = 0.13) or surgical site infections (SSI, p = 0.70) between cohorts. Among SL patients, pancreas injuries portended an increased risk of intraperitoneal abscesses ( p = 0.0002), as did liver injuries in DCL patients ( p = 0.06). Conclusions: DCL was not associated with increased enteric leaks, ECF, SSI, or intraperitoneal abscesses despite nearly two-thirds having delayed repair. Despite this being a multicenter study, it is underpowered, and a prospective trial would better demonstrate risks of DCL in colon trauma. Level of Evidence: Therapeutic study, level IV.